Класифікація рибопропускних споруд - Мельничук, Інна (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
Тези доповіді присвячені класифікації рибопропускних споруд, опису принципів їхньої роботи, області застосування, перевагам та недолікам даних споруд. The report is devoted to the classification of fish passes structures, a description of the principles of their operation, the field of application, advantages and disadvantages of these structures.